"Do I understand you right then?": (re)formulations of users' initial problem descriptions in social services' online chat. (November 2022) - Thell, Nataliya
In anonymous online text-based counselling provided by social services, counsellors face specific communicative and professional challenges. Among other things, they need to ensure that they have understood the chat users correctly in order to provide relevant information and advice. The paper studies how counsellors check their understanding of users' situations by using formulations, namely, summarising and rephrasing users' initial problem descriptions. The data consists of chat logs from 56 web-based counselling sessions provided by social services in Sweden. Conversational analysis is used to examine the functions of chat counsellors' formulations. Analyses show that counsellors reformulate users' initial requests to establish a joint understanding of the users' situations and help requested. Three distinct functions of the initial formulations are identified: recasting requests in the institutional terms of social services, clarifying ambiguity in the user's initial posts and affiliating with the user.